Correction: SARS-CoV-2 seroepidemiology in Cape Town, South Africa, and implications for future outbreaks in low-income communities. - Hannah Hussey; Helena Vreede; Mary-Ann Davies; Alexa Heekes; Emma Kalk; Diana Hardie; Gert van Zyl; Michelle Naidoo; Erna Morden; Jamy-Lee Bam; Nesbert Zinyakatira; Chad M Centner; et al. (PLOS Global Public Health)
[This corrects the article DOI: 10.1371/journal.pgph.0003554.].